Reading instructions for an early printed map of the Chinese Empire: a digital reconstruction - De Weerdt, H (2009)
This slide show reconstructs the instructions embedded in the supplemental notes to the survey map published in the earliest extant printed atlas of the Chinese Empire (ca. 1130).